Pengaruh Pergaulan Teman Sebaya dan Pola Asuh Orang Tua terhadap Kedisiplinan - Dewi Nariyah; Dedi Romli Triputra; Didik Tri Setiyoko (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of peer relationships and parenting patterns on the discipline of fifth grade students at SD Negeri Cipelem 02. This type of research uses a quantitative correlation approach. This is done to find the presence or absence of a relationship between variables. The technique of collecting data for peer association and parenting is in the form of a questionnaire with the tool used is a Likert scale. The total population in the study was the entire class V. The sampling technique in this study used a saturated sample technique with a total of 39 students in class V. This study was analyzed using the t test using the SPSS 16 program, with the t test on Peer Association (X1) against Discipline (Y) with the results obtained, namely the sig value of 0.000 so that the sig value <0.05 thus Ho1 is rejected and Ha1 is accepted, which means X1 has an influence on Y. In the Parenting Pattern variable (X2) on Discipline (Y) with the results The result obtained is the sig value of 0.000 so that the sig value is <0.05, thus Ho2 is rejected and Ha2, which means X2 has an influence on Y. Then the f test of Peer Association (X1) and Parenting Parenting (X2) on Discipline (Y ) with the results obtained a significant level of 5% (0.05) and ftable of 3.25 obtained fcount of 8.335 thus Ho3 is rejected and Ha3 is accepted with a determinant coefficient ASI is 0.646, which means that peer association and parenting have an influence of 65% on the discipline of fifth grade students at SD Negeri Cipelem 02.